(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
Safa Duschanov was born in 1939 in the city of Urganch, Khorezm region. He lost his family when he was young, so he lived in an orphanage in Khiva. From a young age, he had a strong love for visual arts and painting. Safa Duschanov is a versatile artist who works in various genres